Judicial balacing of parental objection to medical treatment on the basis of religious beleifs and children right to life in Nigeria (2022)
Children being vulnerable, have special protection uudei the law through their parents 01 guardian who are responsible for them: and make decision- fot them because they lack legal capacity One of these decisions a parent/gunrdian makes i- determining the religion of a child. Once the parent guardian chooses the religion of the child, the child may become bound by its practices throughout childhood While the right of parents to determine the religion of theii children is recognised by domestic regional and international laws, the way courts in Nigeria treat this recognition suggests that the right is nol absolute. This paper adopts the doctrinal methodology 111 interrogating the extent to which Nigerian Courts permit the observation by a child oftlie religious practices ofhis/lier parent in relation to submission to medical treatment in order to protect the child's right to life This papei argues that law and morality are media of social control but have their convergence and divergence. It further argues that sanctity of human life which for many forbids suicide, requites that even adults should not be allowed to object to medical treatment which refusal may lesult in death which can be seen as "disguised suicide" These authors examined the Supreme Court decision m Medical Dental Practitioners Disciplinary Council v Okonkwo and found that: Nigerian Courts recognise parent light to choose their children religion and practices however, any religious practice prejudicial to the child based on the "best interest" principle provided under the Child Right Act and its States equivalent will be jettisoned It examines the practice til Britain and Canada and draw lessons for Nigeria. This paper recommends public enlightenment prohibition of harmful religious beliefs such as objection to life-saving medical procedure by parents for minors as means of balancing parents/guardian right to choose their children religions beliefs and preservation of the children right to life.